2002
DOI: 10.2151/jmsj.80.229
|View full text |Cite
|
Sign up to set email alerts
|

Extratropical Transformation of Typhoon Vicki (9807): Structural Change and the Role of Upper-tropospheric Disturbances.

Abstract: Extratropical transformation of Typhoon Vicki (9807) is diagnosed in relation to its environment, particularly with respect to interactions with upper tropospheric disturbances, using the gridded dataset of global analysis (GANAL) produced by the Japan Meteorological Agency. TY Vicki made landfall on Japan with its maximum intensity on 22 September 1998, causing damage with strong winds. Vicki lost the diabatically generated potential vorticity (PV) anomaly at 00UTC 23 September 1998, when it was supposed to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…As described in Section 1, the effect of an upperlevel trough in an extratropical cyclone is a key issue in studies of ETs (e.g., Sinclair 1993;Kitabatake 2002). In the case of Bebinca, an upper-level trough was also located near the storm.…”
Section: Effect Of Upper-level Troughmentioning
confidence: 99%
“…As described in Section 1, the effect of an upperlevel trough in an extratropical cyclone is a key issue in studies of ETs (e.g., Sinclair 1993;Kitabatake 2002). In the case of Bebinca, an upper-level trough was also located near the storm.…”
Section: Effect Of Upper-level Troughmentioning
confidence: 99%
“…In particular, as a typhoon approaches the midlatitudes, the rainfall resulting from the direct and indirect influence of the typhoon is closely related to the interactions between the synoptic-scale environment and the topography. Kitabatake [2002] found that an organized rainfall region was induced in the northern semicircle of a typhoon by an extratropical transformation of the typhoon related to upper troposphere disturbances; the rainfall region was limited southwest of the cyclone center. Atallah and Bosart [2003] showed that the baroclinic zone between the juxtaposition of a cold-core potential vorticity (PV) anomaly associated with the midlatitude trough and a warm-core PV anomaly associated with a tropical cyclone provided sufficient precipitation in a region favorable for deep isentropic ascent.…”
Section: Introductionmentioning
confidence: 99%
“…He also described the cold-front generation to the southwest of the transformed cyclone. Kitabatake (2002) described, in a case study on the extratropical transformation of TY Vicki in 1998, that ''to the west of the cyclone, middle tropospheric dry air, which was accompanied by the approaching upper tropospheric disturbance, descended into the cyclone and induced active convection to just west of the cyclone eye.' ' Suzuki (2000) described the characteristics of the extratropical transition of tropical cyclones in satellite imagery for 22 cases.…”
Section: Discussionmentioning
confidence: 99%